Knowledge of and Attitude towards Primary Healthcare among Undergraduate Medical Students - Almas Khattak; Rabia Khattak; Maria Mufti; Haseeba Mukhtar (Gandhara University, 2022)
OBJECTIVES: To assess undergraduate medical students' knowledge of and their attitudes towards primary healthcare and to compare the knowledge and attitudes of students in public and private medical colleges as well as between different demographic groups of students. METHODOLOGY: A descriptive cross-sectional survey was conducted in public and private medical colleges after an ethical approval was granted. Data was collected from 201 undergraduate medical students through a validated (by Chalmers et al. 1997) Primary Health Care Questionnaire (PHCQ) utilizing an online data collection platform of Google Forms. The link to Google Form was distributed via emails and social media links of participating colleges. Data was exported from Google Form into SPSS version 24 and analyzed. RESULTS: The total knowledge score of students ranged from 8 to 17 with the mean knowledge score of 12.62 (SD: 1.398). The total attitude score ranged from 59 to 82 for all the participants with the mean attitude score of 71.12 (SD=4.382). Comparison of knowledge scores showed higher scores in females than males (p=0.004), and significantly higher attitudes scores among private medical students than public (p=0.037). CONCLUSION: Medical students' gender and setting of their medical studies showed significant influence on their knowledge of and attitudes towards primary healthcare.